MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN VIDEO PEMBELAJARAN MATERI BUNYI DAN SIFATNYA KELAS V SDN 89 SIPATANA - Sriyanti K. Umar; Irvin Novita Arifin; Gamar Abdullah; Abdul Haris Panai; Meylan Saleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The formulation of the problem in this research is "Can the application of the Discovery Learning model assisted by Video Learning on sound material and its properties improve the learning outcomes of class V students at SDN 89 Sipatana?". The aim of this research is to improve student learning outcomes through the application of the Discovery Learning model assisted by Video Learning on sound material and its characteristics for class V SDN 89 Sipatana. The research method used is Classroom Action Research (PTK) using observation, test and documentation data collection techniques with the research subjects being class V students with a total of 19 students. The indicator of the success of the action is marked by a minimum of 80% of students' overall learning outcomes reaching a KKTP score of 75. The research results show that the application of the Discovery Learning model assisted by Learning Videos applied in class V at SDN 89 Sipatana can improve student learning outcomes. In cycle I, student learning outcomes that met the minimum completeness standard were 57.89%. Then it increased to 84.21%, meaning there was an increase from cycle I to cycle II of 26.38%. It can be concluded that the application of the Discovery Learning model assisted by Learning Videos can improve student learning outcomes in the science and science learning content in class V at SDN 89 Sipatana.